A constraint optimization approach to model based supervisory control for renewable energy integration in commercial buildings - Parthiban Palani (2016)
With the recent focus on climate protection amidst rising energy prices, the need of the hour is the utilization of renewable energy sources. Many countries are already on the right track, however, new technical and economical challenges arise with the penetration of renewable energy sources. Once such challenge arises in commercial buildings having huge energy expenses and at the same time trying to be self sufficient. A huge portion of the energy expense in commercial buildings in countries with hot climate can be attributed to space cooling. An effective way to control and integrate the space cooling with a renewable source such as a PV plant has been demonstrated in this thesis. A hypothetical building with a water cooled chiller unit and a solar PV plant has been modeled. A supervisory controller has been designed to provide set points to the chiller unit considering the output of the PV plant and the price of electricity from the local grid. This supervisory control problem has been formulated as a standard linear optimization problem. Three model based control methods have been proposed to design the supervisory controller. The supervisory controller designed according to the three methods have been tested on the building model for different scenarios and the results have been compared. All the modeling, designing and simulations have been done in Matlab/Simulink.
Keywords: Renewable Energy Integration; Commercial Building